Managing cultural tourism in post-conflict areas: the Kurdistan Federal Region, Iraq - Braim, Kadhim; McCabe, Scott; Rickly, Jillian M.; Gadi, Mohamed (College of Tourism and Hotel Management (Nicosia, Cyprus), 2017)
Conflict and post-conflict areas often suffer several challenges regarding tourism development owing to poor infrastructure, low investment, a lack of appropriate tourism management planning, and poor implementation mechanisms. Much research has been undertaken regarding cultural tourism management issues, challenges and sustainability, yet there is a lack of knowledge on how post-conflict issues affect cultural tourism planning and management. The aim of this paper is to understand the challenges posed in post-conflict regions, for cultural tourism development and to propose solutions and recommendations for successful, competitive and sustainable cultural tourism sectors. The context for the research is the Kurdistan Federal Region (KFR) in Iraq. The study revealed several challenges facing cultural tourism in KFR. The paper reports data from a series of focus groups conducted with residents and tourists, and a number of in-depth interviews with tourism policymakers and experts in KFR.